2022
DOI: 10.1177/26350106211072203
|View full text |Cite
|
Sign up to set email alerts
|

2022 National Standards for Diabetes Self-Management Education and Support

Abstract: Purpose: The National Standards for Diabetes Self-Management Education and Support (DSMES) provide guidance and evidence-based, quality practice for all DSMES services. Due to the dynamic nature of health care and diabetes research, the National Standards are reviewed and revised approximately every 5 years by key stakeholders and experts within the diabetes care and education community. For each revision, the Task Force is charged with reviewing the current National Standards for appropriateness, relevance, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
64
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 130 publications
0
64
0
2
Order By: Relevance
“…The results from the 6th National Health Examination Survey (2019–2020) in Thailand revealed that only 26.3% of patients with diagnosed diabetes had good glycemic control as measured by fasting glucose levels 16 . Besides antihyperglycemic medications and insulin, diabetes self‐management education and support (DSMES) is recognized as an important strategy in managing diabetes and achieving glycemic control 17 . Unfortunately, it was estimated that <5% of Medicare Beneficiaries in the US utilized DSMES services 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The results from the 6th National Health Examination Survey (2019–2020) in Thailand revealed that only 26.3% of patients with diagnosed diabetes had good glycemic control as measured by fasting glucose levels 16 . Besides antihyperglycemic medications and insulin, diabetes self‐management education and support (DSMES) is recognized as an important strategy in managing diabetes and achieving glycemic control 17 . Unfortunately, it was estimated that <5% of Medicare Beneficiaries in the US utilized DSMES services 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have proven the benefits of Diabetes Self-Management Education and Support (DSMES), which include improved clinical outcomes and quality of life while reducing hospitalizations and health care costs [ 10 , 11 ]. To demonstrate the benefits of DSMES, it is important to measure relevant clinical outcomes, patient-reported outcomes, and psychosocial and behavioral outcomes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the rise in diabetes, prediabetes, and cardiometabolic conditions, a competent and diverse interprofessional care team is necessary to address US and global health care trends and to provide evidence-based care and integrated education and training that meets clinical practice guidelines. 4-7…”
mentioning
confidence: 99%
“…Given the rise in diabetes, prediabetes, and cardiometabolic conditions, a competent and diverse interprofessional care team is necessary to address US and global health care trends and to provide evidencebased care and integrated education and training that meets clinical practice guidelines. [4][5][6][7] The Association of Diabetes Care & Education Specialists (ADCES) is an interprofessional membership organization that includes nurses, dietitians, pharmacists, health educators, and other health care professionals who integrate person-centered care and education into clinical management. The ADCES mission and strategic focus support specialty practice that spans prediabetes, diabetes, and cardiometabolic conditions, with goals to connect the health care team and offer holistic, accessible, and effective care integrated with essential education/training components.…”
mentioning
confidence: 99%